An Extensive Result Containing Certain Analytic Functions and Some of Its Implications - Irmak, Hüseyin (Sarajevo Journal of Mathematics, 2022)
In this note, an extensive result consisting of analytic functions will firstly be constituted and it will then be proven by means of the well-known assertions given in [12, 15]. As it was detailed in the works in [3, 5, 7, 16, 20], several special results concerning analytic and geometric properties of certain complex valued functions will also be created as some of related implications of the main result. Finally, for other possible implications pertaining to the results given by [4, 7, 9, 13, 24, 25], a large number of conclusions and recommendations will be pointed out in the last section.